Traditional methods of processing livestock feed to reduce antinutrient factor content: a brief review - yanuartono - -; Alfarisa Nururrozi; Soedarmanto Indarjulianto; Hary Purnamaningsih; Slamet Raharjo (Jurnal Ilmu Ternak, 2019)
Anti-nutrients or anti-nutritional factors may be defined as those substances generated in natural feedstuffs by the normal metabolism of species and by different mechanisms. Anti-nutritonal factors are substances which either by themselves or through their metabolic products, interfere with feed utilization and affect the health and production of animal or which act to reduce nutrient intake, digestion, absorption and utilization and may produce other adverse effects Removal of undesirable components is essential to improve the nutritional quality of livestock feed and effectively utilize their full potential as ruminants feed ingredient. It is widely accepted traditionally methods that simple and inexpensive processing techniques are effective methods of achieving desirable changes in the composition of forage, legume and grain. Chopping, grinding, soaking, roasting, germination and chemical treatment could improve the quality of feed because of the reduce, removal or inactivation of some anti-nutritional factors. Traditional methods, both single and combination, have been proven capable of working by small-scale farmers in developing countries and can reduce the operational costs of processing feed ingredients to reduce ANF content and improve the quality of nutritional value.Keywords : anti nutritional factors, feedstuffs, traditionally methods, inexpensive